2021
DOI: 10.1080/08897077.2021.1932697
|View full text |Cite
|
Sign up to set email alerts
|

A Call for Training Graduate Medical Students on Harm Reduction for People who Inject Drugs

Abstract: There is a lack of standardized education on topic of harm reduction for graduate medical students. In order to fill this curricular gap, we delivered a two-hour pilot training introducing local community harm reduction organizations and harm reduction ideology and strategies for people who inject drugs to graduate medical students at Boston University. We used pre-post survey design to evaluate attendee demographic characteristics and training efficacy. We matched 29 attendees responses, 69% were first and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…-In-person synchronous Naloxone demonstration No Naloxone, overdose etiology/physiology, overdose risk, overdose identification No evaluation of student learning was reported Not Available, but based on AHA Opioid Associated Life-Threatening Emergency Algorithm Jawa 2020 [ 54 ] Boston Medical Center at Boston University School of Medicine IM PGY1 (pilot) Medical and surgical PGY and fellows (expanded program) -Voluntary (expanded program) -15 min. -In-person synchronous Didactics, small group discussion, naloxone demonstration No Naloxone, Good Samaritan laws, overdose etiology/physiology, overdose identification 1) Comfort administering naloxone ( pre/post – 1 month )* 2) Comfort counseling patients on naloxone use ( pre/post – 1 month )* 3) Naloxone prescribing behavior ( pre/post – 1 month ) Fully Available in MedEd Portal Jawa 2021 [ 55 ] Boston University School of Medicine MS1, MS2, medical masters students, PA students, dental students -Voluntary -2 hr. -In-person synchronous Didactics, naloxone demonstration, local organizations Yes Overdose prevention, naloxone, safer injection, SSPs, overdose etiology/physiology, overdose risk, overdose identification, MOUD, infectious complications 1) Comfort with harm reduction ideology ( pre/post )* 2) Knowledge on safe injection technique ( pre/post )* 3) Comfort and knowledge on administering naloxone ( pre/post )* Not Available Klapheke 2017 [ 56 ] University of Central Florida College of Medicine MS3 psychiatry clerkship -Mandatory -30-50 min.…”
Section: Resultsmentioning
confidence: 99%
“…-In-person synchronous Naloxone demonstration No Naloxone, overdose etiology/physiology, overdose risk, overdose identification No evaluation of student learning was reported Not Available, but based on AHA Opioid Associated Life-Threatening Emergency Algorithm Jawa 2020 [ 54 ] Boston Medical Center at Boston University School of Medicine IM PGY1 (pilot) Medical and surgical PGY and fellows (expanded program) -Voluntary (expanded program) -15 min. -In-person synchronous Didactics, small group discussion, naloxone demonstration No Naloxone, Good Samaritan laws, overdose etiology/physiology, overdose identification 1) Comfort administering naloxone ( pre/post – 1 month )* 2) Comfort counseling patients on naloxone use ( pre/post – 1 month )* 3) Naloxone prescribing behavior ( pre/post – 1 month ) Fully Available in MedEd Portal Jawa 2021 [ 55 ] Boston University School of Medicine MS1, MS2, medical masters students, PA students, dental students -Voluntary -2 hr. -In-person synchronous Didactics, naloxone demonstration, local organizations Yes Overdose prevention, naloxone, safer injection, SSPs, overdose etiology/physiology, overdose risk, overdose identification, MOUD, infectious complications 1) Comfort with harm reduction ideology ( pre/post )* 2) Knowledge on safe injection technique ( pre/post )* 3) Comfort and knowledge on administering naloxone ( pre/post )* Not Available Klapheke 2017 [ 56 ] University of Central Florida College of Medicine MS3 psychiatry clerkship -Mandatory -30-50 min.…”
Section: Resultsmentioning
confidence: 99%
“…Given known barriers of healthcare-related stigma [ 32 , 33 ] and lack of standardized medical education on harm reduction practices [ 34 ], we found that coupling clinician and staff training with on-site kit distribution facilitated the adoption of our intervention as a new clinic standard of care. We used multiple implementation strategies to communicate a shared vision to change our clinic culture to embrace a patient-centered approach to care grounded in the principles of relational harm reduction [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond core curricular integration, we also invite students to complete the form via HMS distribution listservs and at the end of a voluntary extracurricular event that educates attendees on harm reduction techniques, including the use of naloxone [ 13 ].…”
Section: Methodsmentioning
confidence: 99%